2020
DOI: 10.1186/s40035-020-00198-y
|View full text |Cite
|
Sign up to set email alerts
|

Altered levels of CSF proteins in patients with FTD, presymptomatic mutation carriers and non-carriers

Abstract: Background: The clinical presentations of frontotemporal dementia (FTD) are diverse and overlap with other neurological disorders. There are, as of today, no biomarkers in clinical practice for diagnosing the disorders. Here, we aimed to find protein markers in cerebrospinal fluid (CSF) from patients with FTD, presymptomatic mutation carriers and non-carriers. Methods: Antibody suspension bead arrays were used to analyse 328 proteins in CSF from patients with behavioural variant FTD (bvFTD, n = 16) and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“… 47 , 48 , 49 , 50 , 51 Neurofilaments are important for the stability and function of neurons and we have previously reported higher levels of the medium subunit, NEFM, in CSF from FTD patients. 52 In another study, we identified increased levels in plasma from ALS patients compared with controls. 53 Further studies will elucidate the potential added value of NEFM in relation to NEFL and NEFH.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“… 47 , 48 , 49 , 50 , 51 Neurofilaments are important for the stability and function of neurons and we have previously reported higher levels of the medium subunit, NEFM, in CSF from FTD patients. 52 In another study, we identified increased levels in plasma from ALS patients compared with controls. 53 Further studies will elucidate the potential added value of NEFM in relation to NEFL and NEFH.…”
Section: Discussionmentioning
confidence: 88%
“… 63 In addition, a previously in‐house developed NEFM sandwich assay showed a strong correlation to the single binder data (rho > 0.82). 52 …”
Section: Discussionmentioning
confidence: 99%
“…The transmembrane protein TMEM132D is highly expressed in the brain (60) and has been proposed to serve as an oligodendric cell surface marker (61) with cell-adhesion functions (62), although its main function still remains unknown. To our knowledge TMEM132D has not been studied in the context of AD but we previously observed altered levels in patients with frontotemporal dementia (32). Other membrane bound proteins that showed strong associations to tau were CEND1, myelin oligodendrocyte glycoprotein (MOG), PIK3IP1 and VASN, which have various functions relevant to cell-cycle regulation, cell-adhesion and T-cell activation (63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 97%
“…Read-out was done in a FlexMap3D instrument (Luminex Corporation) and results reported as median uorescence intensities per bead identity and sample, calculated from at least 30 measured beads. More detailed explanations on experimental procedures can be found elsewhere (25,32).…”
Section: Protein Pro Lingmentioning
confidence: 99%
“…The transmembrane protein TMEM132D is highly expressed in the brain (57) and has been proposed to serve as an oligodendric cell surface marker (58) with cell-adhesion functions (59), although its main function still remains unknown. To our knowledge TMEM132D has not been studied in the context of AD but we previously observed altered levels in patients with frontotemporal dementia (32). Other membrane bound proteins that showed strong associations to tau were CEND1, myelin oligodendrocyte glycoprotein (MOG), PIK3IP1 and VASN, which have various functions relevant to cell-cycle regulation, cell-adhesion and T-cell activation (60)(61)(62)(63).…”
Section: Discussionmentioning
confidence: 97%